SOCIAL MEDIA MANAGEMENT IN OPTIMIZING THE BRANDING OF ISLAMIC EDUCATIONAL INSTITUTIONS - Isnanu Rida Saputri; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
In the ever growing digital era, Islamic educational institutions are required to be able to adapt to changes in information and communication technology in order to maintain their existence and increase their competitiveness. Social media has become one of the most influential communication instruments in shaping public perception and trust in an institution, including Islamic educational institutions. However, many madrasah have not made optimal use of social media as a planned and systematic means of branding. The purpose of this research is to study the method of optimizing social media as a branding tool for Islamic educational institutions in the midst of competition between educational institutions in the modern era. Social media is considered not only as a source of information but also as a strategic tool to improve the public's image, reputation, and trust in Islamic educational institutions. A qualitative approach to literature is used in this study; Data collection techniques are used to conduct a review of relevant scientific books and journals, which are then analyzed through content analysis. The results show that the consistency of digital identity, educational and religious content, and responsive two-way communication are the factors that determine the success of branding. Therefore, the regular use of social media and based on Islamic principles is the key to strengthening the madrasah brand in a sustainable manner.